Application of ¹³⁷Cs technique for studying soil erosion in agricultural farmland, Cameron Highlands, Pahang, Malaysia / Che Yasmin Amirudin - Amirudin, Che Yasmin (2015)
¹³⁷Cs has been utilized as a marker for the study of the erosion and redistribution of soil materials. Nuclear bomb testing fallout ¹³⁷Cs is potentially useful as a marker of translocation of surface materials due to non-exchangeability of the cation once it comes into contact with soil particles. The soil redistribution at the sloping area become one of the top concern for planters since it will affect the fertilizers usage and may cause landslide. The study area was in eleven sloping area and a forest nearby the Bharat Tea Plantation, Cameron Highlands, Pahang, Malaysia. The area was selected in order it will provide information on the improvement of soil conditions and cost reduction of fertilizer consumption after the measurements of redistribution rate obtained. The aims of this reseacrh are to determine the erosion and deposition rate of the study areas by using environmental radionuclide applied to two conversion models, Proportional Model (PM) and Mass Balance Model (MBM) after measurements of ¹³⁷Cs activity concentration from the inventory. The soil profile were collected by using scrapper plate at top, center and bottom of eleven sloping areas and three undisturbed site. In every location, disturbed and undisturbed site, one core of hand auger dig was collected for soil basic parameter analysis. The ¹³⁷Cs activity concentration was measured using low background coaxial hyper pure germaniumdetector gamma spectrometer based on ¹³⁷Cs gamma energy peak at 661.66 keV. The selected physical properties of soil, which is bulk density, texture, organic matter content and pH were carried out the analysis. The results shows that the erosion was most occured at the top of the slope, and the depostion was almost occured at the bottom of the slope. The deposition of soil, or the soil gain proved there was a movement of erosion occured at the top of the slope and falled down to the bottom location. Results obtained by PM and MBM were found to be consistent to one another. The highest erosion rate was found at location top of Slope 6 with 62.42 t ha⁻¹ yr⁻¹ by using the PM and 146.41 t ha⁻¹ yr⁻¹by using MBM. The lowest erosion rate was at Slope 10 top with 1.54 t ha⁻¹ yr⁻¹using PM and 1.56 t ha⁻¹ yr⁻¹by using the MBM. Meanwhile, the highest deposition was occured at Slope 1, center location with 216.82 t ha⁻¹ yr⁻¹using the PM and 97.51 t ha⁻¹ yr⁻¹by using the MBM. The lowest deposition showed at Slope 2 center location with 0.05 t ha⁻¹ yr⁻¹for both models used. The results of redistribution rate in this Bharat Tea Plantation were comparable values to that study around Asia by using the conventional methods.